Increased numbers of bone marrow‐derived cells in parathyroid adenoma. (September 2014) - Grabmaier, Ulrich; Brandl, Lydia; Kreiner, Julia; Negele, Thomas; Huber, Bruno C.; Rimmbach, Christian; David, Robert; Brunner, Stefan
Abstract Background In primary hyperparathyroidism (PHPT), the increased levels of parathyroid hormone (PTH) result in mobilisation of bone‐marrow‐derived cells (BMCs) into peripheral blood. However, the fate of these cells is still unknown. Materials and methods In this study, we sought to investigate cells with typical surface markers of BMCs within parathyroid adenomas (PA) of patients with primary hyperparathyroidism. We therefore investigated PA and normal parathyroid glands (NPG) of 15 patients with PHPT by immunohistochemistry and PCR. Results mRNA levels for CD31, CD34 and CD45 were significantly increased in PA compared to NPG. Immunohistochemical staining for CD31 and CD34 revealed a significantly higher vessel density in PA. Furthermore, scattered single cells expressing CD31, CD34 or CD45 were significantly augmented compared to normal parathyroid glands and directly correlated with vessel density. mRNA levels of SDF‐1 was increased whereas its major inhibitor dipeptidylpeptidase IV (DPP IV) is decreased in PA, suggesting that the SDF‐1 axis plays a role in the migration of BMCs into PA. Conclusion These data indicate a possible role of BMCs in the pathophysiology of PA of patients with PHPT.